G-EYE advanced colonoscopy for improved polyp detection rates – a randomized tandem pilot study with different endoscopists - Rey, Johannes Wilhelm; Dümcke, Sebastian; Haschemi, Jafer; Tresch, Achim; Borger, Dietmar; Kirchner, Ann-Christin; Teubner, Daniel; Kiesslich, Ralf; Hoffman, Arthur (Zeitschrift für Gastroenterologie, 2018)
Background and aims The most commonly missed polyps in colonoscopy are those located behind haustral folds. The G-EYE system is a standard colonoscope consisting of re-processable balloon at its distal tip. The G-EYE balloon improves the detection of polyps by straightening the haustral folds. In our back-to-back tandem study, we aimed to determine whether and to what extent the G-EYE system could reduce adenoma miss rates in screening colonoscopy.Methods Patients referred to colonoscopy were randomized into 2 groups. Group A underwent a standard colonoscopy (SC) followed by balloon colonoscopy (BC), and Group B underwent BC followed by SC. In this randomized tandem study, the investigator’s level of training and the endoscopists themselves were changed after each withdrawal. Each endoscopist was blinded to the results of the first withdrawal.Results Fifty-eight patients were enrolled and randomized into 2 groups with similar baseline characteristics. Nine patients were excluded from the study. Twenty-five patients underwent SC followed by BC while 24 underwent BC followed by SC. The adenoma miss rate for SC was 41 %, with an additional detection rate of 69 % for BC (ratio 1.69). The overall miss rate for polyps was 60 % for SC, with an additional detection rate of 150 % for BC (ratio 2.5). Experienced investigators who used BC were able to identify an additional 7 polyps while inexperienced investigators.Conclusions Although our results could not clearly confirm that BC improves adenoma detection, the investigator’s experience appears to be a major determinant of the adenoma detection rate.
Keywords: balloon colonoscopy; polyp detection rate; polyp miss rate; adenoma detection rate; interval colorectal cancer